Complex public administration mechanisms of the Military organization of Ukraine - Protasenko, К. О. (Honor and Law, 2019)
The basic elements and the structure of the complex public administration mechanism of the military organization of Ukraine are analyzed. The main ways of the public administration mechanisms efficiency enhancement of the military organization of Ukraine are proposed.